Interaction of iron phthalocyanine with the graphene/Ni(111) system - Massimi, Lorenzo; Lisi, Simone; Pacilè, Daniela; Mariani, Carlo; Betti, Maria Grazia (Beilstein Journal of Nanotechnology, 2014)
Graphene grown on crystalline metal surfaces is a good candidate to act as a buffer layer between the metal and organic molecules that are deposited on top, because it offers the possibility to control the interaction between the substrate and the molecules. High-resolution angular-resolved ultraviolet photo electron spectroscopy (ARPES) is used to determine the interaction states of iron phthalocyanine molecules that are adsorbed onto graphene on Ni(111). The iron phthalocyanine deposition induces a quenching of the Ni d surface minority band and the appearance of an interface state on graphene/Ni(111). The results have been compared to the deposition of iron phthalocyanine on graphene/Ir(111), for which a higher decoupling of the organic molecule from the underlying metal is exerted by the graphene buffer layer.
Keywords: angular-resolved photo-electron spectroscopy (ARPES); buffer layer; graphene; molecule–substrate interaction

(untitled) - Bogani, L.; Wernsdorfer, W. (Nat. Mater., 2008)

(untitled) - Coe, S.; Woo, W.-K.; Bawendi, M.; Bulović, V. (Nature, 2002)

(untitled) - Bao, Z.; Lovinger, A. J.; Dodabalapur, A. (Appl. Phys. Lett., 1996)

(untitled) - Forrest, S. R. (Chem. Rev., 1997)

(untitled) - Liao, M.-S.; Scheiner, S. (J. Chem. Phys., 2001)

(untitled) - Gargiani, P.; Angelucci, M.; Mariani, C.; Betti, M. G. (Phys. Rev. B, 2010)

(untitled) - Betti, M. G.; Gargiani, P.; Frisenda, R.; Biagi, R.; Cossaro, A.; Verdini, A.; Floreano, L.; Mariani, C. (J. Phys. Chem. C, 2010)

(untitled) - Geim, A. K.; Novoselov, K. S. (Nat. Mater., 2007)

(untitled) - Batzill, M. (Surf. Sci. Rep., 2012)

(untitled) - Avdoshenko, S. M.; Ioffe, I. N.; Cuniberti, G.; Dunsch, L.; Popov, A. A. (ACS Nano, 2011)

(untitled) - Dedkov, Y. S.; Fonin, M. (New J. Phys., 2010)

(untitled) - Pletikosic, I.; Kralj, M.; Pervan, P.; Brako, R.; Coraux, J.; N’diaye, A.; Busse, C.; Michely, T. (arXiv preprint arXiv:0807.2770, 2008)

(untitled) - Scardamaglia, M.; Lisi, S.; Lizzit, S.; Baraldi, A.; Larciprete, R.; Mariani, C.; Betti, M. G. (J. Phys. Chem. C, 2013)

(untitled) - Dou, W.; Huang, S.; Zhang, R.; Lee, C. (J. Chem. Phys., 2011)

(untitled) - Wei-Guo, Y.; Dan, L.; Xiao-Feng, P.; Wei-Dong, D. (Chin. Phys. B, 2013)

(untitled) - Dou, W.; Yang, Q.; Lee, C.-S. (Appl. Phys. Lett., 2013)

(untitled) - Uihlein, J.; Peisert, H.; Glaser, M.; Polek, M.; Adler, H.; Petraki, F.; Ovsyannikov, R.; Bauer, M.; Chassé, T. (J. Chem. Phys., 2013)

(untitled) - Grüneis, A.; Kummer, K.; Vyalikh, D. V. (New J. Phys., 2009)

(untitled) - Lahiri, J.; Miller, T. S.; Ross, A. J.; Adamska, L.; Oleynik, I. I.; Batzill, M. (New J. Phys., 2011)

(untitled) - Patera, L. L.; Africh, C.; Weatherup, R. S.; Blume, R.; Bhardwaj, S.; Castellarin-Cudia, C.; Knop-Gericke, A.; Schloegl, R.; Comelli, G.; Hofmann, S.; Cepek, C. (ACS Nano, 2013)

(untitled) - Gamo, Y.; Nagashima, A.; Wakabayashi, M.; Terai, M.; Oshima, C. (Surf. Sci., 1997)

(untitled) - Varykhalov, A.; Marchenko, D.; Sánchez-Barriga, J.; Scholz, M.; Verberck, B.; Trauzettel, B.; Wehling, T.; Carbone, C.; Rader, O. (Phys. Rev. X, 2012)

(untitled) - N’Diaye, A. T.; Coraux, J.; Plasa, T. N.; Busse, C.; Michely, T. (New J. Phys., 2008)

(untitled) - Starodub, E.; Bostwick, A.; Moreschini, L.; Nie, S.; El Gabaly, F.; McCarty, K. F.; Rotenberg, E. (Phys. Rev. B, 2011)

(untitled) - Bertoni, G.; Calmels, L.; Altibelli, A.; Serin, V. (Phys. Rev. B, 2005)

(untitled) - Sun, Z.; Hämäläinen, S. K.; Sainio, J.; Lahtinen, J.; Vanmaekelbergh, D.; Liljeroth, P. (Phys. Rev. B, 2011)

(untitled) - Kreutz, T. J.; Greber, T.; Aebi, P.; Osterwalder, J. (Phys. Rev. B, 1998)

(untitled) - Yeh, J.; Lindau, I. (At. Data Nucl. Data Tables, 1985)